Peace as societal transformation: intergenerational power-struggles and the role of youth in post-conflict Sierra Leone - Boersch-Supan, J (2012)
Intergenerational solidarity and reciprocity are fundamental building blocks of any society. At the same time, socio-generational groups constantly struggle for influence and authority. In Sub-Saharan Africa, disproportionately male, gerontocratic and patrimonial systems governing economic, social and political life lend a special explosiveness to the social cleavage of generation. This dissertation draws on the concept of the generational contract to explore whether Sierra Leone’s decade-long civil war (1991-2001) – labelled a ‘revolt of youth’ – catalysed changes in the power-asymmetries between age groups. Based on fieldwork conducted between 2007 and 2010, I argue that youth in post-war Sierra Leone question fundamental norms of intergenerational relations and challenge local governance structures demanding changes to the generational contract. Amidst a strong continuity of gerontocratic dominance and counter-strategies from elders, youth draw on organisational forms and a local rights discourse to create spaces for contestation and negotiation. These openings hold potential for long-term rearrangements of societal relations in the medium to long-term future.